Effectiveness of Food Cholesterol Detect (FCD) Application on Total Cholesterol Levels of Hypercholesterolemia Patients - Terati, Terati; Nazarena, Yunita; Shadiq, Ahmad (Poltekkes Kemenkes Jakarta III, 2025)
High cholesterol levels will cause blockages in blood vessels so that circulation is disrupted. The incidence of hypercholesterolemia is still quite high. The Food Cholesterol Detect application is one of the screening tools that can be used to determine the amount of cholesterol intake consumed through food. The purpose of this study was to determine the effectiveness of using the Food Cholesterol Detect application on the total cholesterol levels of patients with hypercholesterolemia. This research design uses quasi-experiments before and after using the application with a one group pre-post test design. Data analysis used univariate and bivariate analysis to see the relationship between the dependent variable (total cholesterol levels of hypercholesterolemia patients) and the independent variable. The characteristics of respondents were mostly in the age group of 30-49 years, approximately 44.3%,. Most of the hypercholesterolemia patients have normal nutritional status based on BMI, namely (50%). Cholesterol levels are mostly female, namely (62.9%) having high borderline total cholesterol levels of 200-239 mg/dl. Cholesterol intake in food consumed shows that all respondents, both men and women, 100% have a high intake of cholesterol in food ≥ 200 mg / hr. There is a difference in the average total cholesterol levels of hypercholesterolemia patients before using the Food Cholesterol Detect Application, which is 234.432 mg/dl, while after use it is 203.892 mg/dl. There is an effect of the effectiveness of the Food Cholesterol Detect Application on reducing total cholesterol levels.